Dimensions of a Life Pleasing to God Based on 1 Thessalonians 4:1–12 - Awenton; Yeremia; Sri Wahyuni (ORTHOTOMEO : Jurnal Penelitian Ilmiah, 2025)
A life pleasing to God represents a theological and ethical calling that requires character transformation and concrete obedience in the life of believers. Based on 1 Thessalonians 4:1–12, the Apostle Paul emphasizes that a life pleasing to God is manifested through holiness, love toward others, and a credible Christian witness within society. This study aims to examine the level of a life pleasing to God and to identify the most dominant dimension shaping congregational practice. Employing a quantitative approach with a survey method, data were collected from members of the Indonesian Gospel Tabernacle Church Eklesia Tumbang Bai using a Likert-scale questionnaire. The data were analyzed through validity and reliability tests, normality testing, confidence interval analysis, and linear regression using SPSS 25. The findings reveal that the level of a life pleasing to God falls within the high category, contradicting the initial hypothesis that predicted a moderate level. Among the three analyzed dimensions, being a good witness emerged as the most dominant factor, with a correlation coefficient of 0.965 and a contribution of 93.1%. These results indicate that behaviors reflecting the character of Christ play a decisive role in shaping a consistent and contextually relevant life pleasing to God within the congregation.